Marketing management : - Howard, John A. (R.D. Irwin, 1963)
Marketing Management to be even easier for getting marketing fundamentals down fast. With interactive key terms, live web links and a search feature that looks in the book and the web, Framework on Inkling is a better way to study marketing.